Романи М. Шолохова і М. Стельмаха: проблеми національної специфіки: автореферат дис. ... канд. філологічних наук: 10.01.05 - Адамович, Анастасія Євгенівна; Адамович, Анастасия Евгеньевна; Adamovych, Anastasiia (My University, 2011)
UK: У дисертації здійснено комплексний системний порівняльний аналіз романістики М. Шолохова і М. Стельмаха (на матеріалі романів “Тихий Дон” і “Хліб і сіль”, “Кров людська – не водиця”), визначено спільне і відмінне у поетиці художньої системи митців з точки зору традицій і новаторства. Вперше у вітчизняному літературознавстві на формально-змістовому рівні здійснено генетичне, типологічне зіставлення творів обох письменників. RU: В диссертации рассмотрен генетический аспект раскрытия характера, который дает возможность более глубоко проанализировать истоки формирования героев как личностей, раскрывает авторскую философию мышления. М. Шолохов рядом с изображением родственной принадлежности персонажей показывает эволюцию личности под влиянием военного времени. Персонажи же М. Стельмаха, ощущая крепкую родственную связь (определенная социальная группа), являются своеобразными выразителями идеалов и стремлений всего украинского народа. EN: The dissertation presents a comprehensive systematic comparative analysis of M. Sholokhov and M. Stelmakh romance philology based on the novels "And Quiet flows the Don " and "Bread and salt", "Human blood is not Water". Common and different aspects in artistic poetics of the authors from the point of tradition and innovation have been defined. First time in our literary criticism typological and genetic comparison of the novels of both writers have been performed at the formal and factual level. Ways of contemporary Ukrainian artistic classics reading were expanded on the background of world literature. Theoretical skill schools of M. Sholokhov and M. Stelmakh were further developed. In addition, there is the scientific importance of the dissertation in the literary texts analysis performed in different aspects.The obtained results promote further study of these novels artistic problems, their intertextuality, integrity and consistency of the artistic texts.
Novels of M. Sholokhov and M. Stelmakh: the problems of national specificity
Романы М. Шолохова и М. Стельмаха: проблемы национальной специфики
Keywords: компаративний аналіз; національна специфіка; історіографія; поетика; типологія; стиль; генетичний аспект; діалого-монологічне мовлення; ретроспекція; портретистка; сюжет; типові обставини; композиція; позасюжетні елементи; авторські відступи; компаративный анализ; национальная специфика; поэтика; типология; историография; стиль; генетический аспект; ретроспекция; портретистика; диалого-монологическая речь; сюжет; типичные обстоятельства; композиция; позасюжетные елементы; авторские отступления; comparative analysis; national specificity; historiography; poetics; typology; style; genetic aspect; retrospection; the dialogue and monologue speech; story; typical conditions; composition; extra plot elements; author retreats